2019
DOI: 10.1186/s12938-019-0657-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): uncertainty quantification of geometric rupture risk parameters

Abstract: BackgroundGeometric parameters have been proposed for prediction of cerebral aneurysm rupture risk. Predicting the rupture risk for incidentally detected unruptured aneurysms could help clinicians in their treatment decision. However, assessment of geometric parameters depends on several factors, including the spatial resolution of the imaging modality used and the chosen reconstruction procedure. The aim of this study was to investigate the uncertainty of a variety of previously proposed geometric parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Additionally, the size of the aneurysm neck was found to be overestimated rather than underestimated. Such overestimation can lead to different flow patterns and misinterpretation of the final results 25,33–35 . As a result of the MATCH 2018, the size of the aneurysm can be cross‐validated to reduce potential segmentation errors, for example, by comparing the resulting 3D model with high‐resolution 2D digital subtraction angiography data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the size of the aneurysm neck was found to be overestimated rather than underestimated. Such overestimation can lead to different flow patterns and misinterpretation of the final results 25,33–35 . As a result of the MATCH 2018, the size of the aneurysm can be cross‐validated to reduce potential segmentation errors, for example, by comparing the resulting 3D model with high‐resolution 2D digital subtraction angiography data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found high variability in the uncertainty of different geometric risk parameters as well as differences in their ability to differentiate between ruptured and unruptured IAs. [14][15][16] Furthermore, for geometric risk parameters with multiple alternative definitions, the specific implementation can affect the discriminative performance of the parameter itself and any derived parameters, as demonstrated by Lauric et al for parameters incorporating IA and neck size. 17 The current study was performed to facilitate optimal selection of geometric rupture risk parameters by identifying geometric parameters, which are good discriminators while also exhibiting low uncertainty.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Altogether more as 40 different geometric risk parameters were proposed [18]. Furthermore, hemodynamic parameters describing aneurysmal flow patterns as well as forces acting on aneurysmal wall such as wall shear stress or oscillatory shear index were proposed to predict aneurysm rupture.…”
Section: Ia Rupture Riskmentioning
confidence: 99%